The Problem of Legal Void and Government Indecisiveness Regarding Environmental Pollution and Damage by Coal Stockpiles - Ahmad Redi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Coal stockpile activities spread across various regions in Indonesia have caused serious environmental problems, especially related to air, water, and soil pollution. Although the impacts are real and ongoing, legal regulations for these activities are still tiniest, even showing a fairly crucial legal vacuum. The absence of specific regulations, binding technical standards, and overlapping authority between government agencies has resulted in weak supervision and law enforcement of coal stockpile business actors. This study uses a normative-empirical legal approach with a qualitative analysis method to examine the forms of legal vacuum in environmental management related to coal stockpiles and their implications for community and ecosystem protection. The research results indicate that comprehensive legal reform is needed, both through the formation of new regulations, strengthening the role of local governments, increasing law enforcement effectiveness, and actively involving the public in environmental supervision. The reform is crucial to realize sustainable and environmentally just mining governance.